Assessment of success rate of endodontic treatment performed by Brazilian undergraduate students - Valera, Marcia Carneiro [UNESP]; Araújo, Maria Amélia Máximo [UNESP]; Fernandes, Aletéia Massula [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; Carvalho, Claudio Antônio Talge [UNESP] (My University, 2012)
Objective: The aim of this paper was to evaluate the success rate of endodontic treatments performed by undergraduate students at São Paulo State University (Brazil). Methods: A random sample of 94 records from 85 patients who received endodontic treatment was analyzed. All evaluated cases undergone endodontic treatment using the same standardized irrigation solutions and intracanal medication. The criteria used to characterize the clinical successful were: no pain, swelling or fistula and complete or partial regression of apical injury, radiographically observed. Kappa's test was used to verify the statistic correlation between treatment, clinical and radiographic success. Results: According to clinical and radiographic evaluation, the success rates were 89.36% and 88.29%, respectively. The statistical analysis indicated that the success of endodontic treatment occurred in 79 (84.04%) of 94 cases (p=0.14). Conclusion: The treatment of teeth with pulp necrosis performed by Brazilian undergraduate students showed, clinically and radiographically, a high level of success.
Keywords: Dentistry students; Endodontics; Treatment failure